KINERJA PEGAWAI: DAMPAK KOMITMEN ORGANISASI DAN KOMPETENSI DENGAN KEPUASAN KERJA SEBAGAI PEMEDIASI (Survey Pada Sekretariat Daerah Kabupaten Sleman Daerah Istimewa Yogyakarta) - Titi Laras; Bambang Jatmiko; Edukasih Wawuru (Jurnal Perilaku dan Strategi Bisnis, 2021)
One of the main functions of government is to provide public services as a manifestation of the general task of government to realize the welfare of the community. Along with this, the development of the state civil apparatus is carried out continuously, so that it can become an efficient and effective, clean and authoritative tool. This research aims to determine the effect of organizational commitment and competence on employee performance mediated by job satisfaction at the regional secretariat of Sleman Regency, Yogyakarta Special Region. In this research using quantitative methods. Placing the sample based on the saturated sampling technique or census with the population in this research being all permanent employees at the regional secretariat of Sleman Regency who visited 137 people. The results of the study indicate that organizational commitment and competence have a positive effect on job satisfaction. organizational commitment and has a positive effect on employee performance. Job satisfaction has a positive effect on employee performance. Job satisfaction is able to mediate the effect of organizational commitment on employee performance. Job satisfaction is able to mediate the influence of competence on employee performance. From this research the authors suggest that the regional secretariat of the Special Sleman Regency, Yogyakarta can optimize organizational commitment, job satisfaction to improve employee performance.